ANALISIS PENGARUH CAPITAL INTENSITY, GROWTH OPPORTUNITY, DAN LEVERAGE TERHADAP KONSERVATISME AKUNTANSI - Kusuma Indawati Halim (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2023)
Applying accounting conservatism correctly will strengthen the dependability of financial reports and enabling stakeholders to use them as a decision-making tool. The advantage of accounting conservatism is that it might give a signal that encourages investors to exercise caution. The purpose of this study was to examine the impact of capital intensity, growth opportunity, and leverage on accounting conservatism. Measurement of the variable capital intensity by means of a comparison of total assets with operating income. The growth opportunity variable is measured using the market/book value of equity, while the leverage variable is measured using a ratio of total debt to total assets. This type of research is a quantitative association study. The research object is aimed at companies that are members of the LQ45 index on the Indonesia Stock Exchange, with a total population of 45 companies. Determination of the sample of this study using porposive sampling method and obtained a sample of 20 companies. Methods of data analysis using multiple linear regression analysis. The test results prove that capital intensity and leverage have a positive effect on accounting conservatism, while growth opportunities have no effect on accounting conservatism